Understanding Primary School English Teachers’ Perspectives on Multicultural Education in Eastern Indonesia - Kakerissa, Wenda Marlin; Toisuta, Emanuela Giovanni (MATAI: International Journal of Language Education, 2025)
This study explores the perspectives of primary school English teachers on multicultural education within the context of Eastern Indonesia, particularly in Ambon City. The research aims to understand how teachers perceive the importance, relevance, and challenges of multicultural education in shaping students’ social awareness and intercultural competence. Using a descriptive qualitative design, data were collected from six primary school English teachers through a ten-item questionnaire consisting of two categories: conceptual understanding and perceived importance of multicultural education. The results reveal that all participants demonstrated a high level of conceptual awareness regarding the value of multicultural education in fostering tolerance, respect, and social harmony among students. However, variations emerged in teachers’ readiness to implement multicultural-based approaches in classroom instruction. While most teachers agreed that integrating local cultural content is essential, a few expressed uncertainty due to limited pedagogical resources and institutional support. Overall, the findings highlight that teachers’ perspectives are shaped not only by theoretical understanding but also by contextual realities of teaching in a culturally diverse environment. The study concludes that strengthening teachers’ professional capacity and institutional support is crucial to bridge the gap between understanding and practice. These findings offer valuable insights for future research and policy development in multicultural and English language education across Indonesia’s diverse regions.